The Cruel Optimism of Racial Justice - Meer, Nasar (Book collections on Project MUSE., 2022)
Looking at examples across anti-racist movements and developments in nationhood/nationalism, institutional racism, migration, white supremacy and the disparities of COVID-19, Nasar Meer argues for the need to move on from perpetual crisis in racial justice to a turning point that might change deep-seated systems of racism.